Active oxygen responsive tegafur-pyropheophorbide conjugate soluble microneedle preparation and application thereof
By developing reactive oxygen-responsive tigafluoro-pyrodemagnesium chlorochloric acid a conjugate soluble microneedle preparation, using micelle-microneedle delivery system and photodynamic technology, the whole body of TF drugs in the treatment process was solved. The problems of sexual toxicity reactions and insufficient bioavailability have achieved more efficient and safe anti-tumor effects.
Patent Information
- Application Number
- CN202311003214.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-02-18
AI Technical Summary
There is a risk of systemic toxicity during the treatment process of existing tegafluoride (TF) drugs, and their bioavailability and efficacy are insufficient.
Develop a reactive oxygen-responsive tigafluoro-pyrodemagnesium chlorochloric acid a conjugate soluble microneedle preparation, combining TF with photosensitizer through micelle-microneedle delivery system, and using photodynamics (PDT) to generate Synergistic anti-tumor effect.
This preparation can reduce side effects while improving the efficacy, realize deep-depending drug delivery of tumors, and enhance anti-tumor effects.
Smart Images

Figure CN119454944A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of pharmaceutical preparations, and in particular relates to an active oxygen responsive tegafur-pyropheophorbide a conjugate soluble microneedle preparation and application thereof. Background Art
[0002] Tegafur (TF) is a uracil anti-metabolite drug with a broad anti-tumor spectrum and good efficacy in treating gastrointestinal tumors, breast cancer, thyroid cancer, etc. It can be used in combination with a variety of anti-cancer drugs for chemotherapy. It is also the first choice of chemical drugs for postoperative and advanced patients. It can be administered orally, topically or intravenously. TF is the precursor of 5-Fluorouracil (5-FU). It is mainly activated by cytochrome P450 in the liver to produce 5-FU and other components that reduce gastrointestinal toxicity, and then distributed throughout the body. Compared with 5-FU, it has a long-lasting effect, good absorption, low toxicity, and high bioavailability. However, TF still has certain toxic side effects and there is still a risk of systemic toxic reactions. Summary of the invention
[0003] The object of the present invention is to overcome the defects of the prior art and provide a reactive oxygen responsive tegafur-pyropheophorbide a conjugate soluble microneedle preparation and its application.
[0004] The technical solution of the present invention is as follows:
[0005] A reactive oxygen responsive tegafur-pyropheophorbide a conjugate soluble microneedle preparation, characterized in that: it is prepared by mixing TF-TA-PPa conjugate micelle solution, PSF, Arg8 and PVP-K90 by centrifugation, wherein:
[0006] The TF-TA-PPa conjugate micelle solution is prepared by dissolving the TF-TA-PPa conjugate and F68 in 55-64°C anhydrous ethanol, adding the solution dropwise to 55-64°C deionized water while stirring, and stirring at room temperature in the dark for 20-25 hours.
[0007] The structural formula of the TF-TA-PPa conjugate is
[0008] In a preferred embodiment of the present invention, the mass ratio of the TF-TA-PPa conjugate to the F68 is 1:5.
[0009] In a preferred embodiment of the present invention, the mass ratio of PSF to PVP-K90 is 1-1.5:8.5-9.
[0010] Further preferably, the mass ratio of PSF to PVP-K90 is 1:9 or 1.5:8.5.
[0011] More preferably, the added amount of Arg8 is 4-6% of the total mass of PSF and PVP-K90.
[0012] Still more preferably, the added amount of Arg8 is 5% of the total mass of PSF and PVP-K90.
[0013] In a preferred embodiment of the present invention, the synthesis route of the TF-TA-PPa conjugate is:
[0014]
[0015] Application of the above active oxygen responsive tegafur-pyropheophorbide a conjugate soluble microneedle preparation in the preparation of an anti-tumor composition.
[0016] An anti-tumor composition, the effective ingredients of which include the above-mentioned active oxygen responsive tegafur-pyropheophorbide a conjugate soluble microneedle preparation.
[0017] In a preferred embodiment of the present invention, the active ingredient is the active oxygen responsive tegafur-pyropheophorbide a conjugate soluble microneedle preparation.
[0018] The beneficial effects of the present invention are:
[0019] 1. The present invention uses a micelle-microneedle drug delivery system to deliver TF, which has certain toxic side effects, to avoid systemic toxic reactions, and combines it with a photosensitizer. With the help of PDT, the chemotherapy of TF and the ROS generated by PDT produce a synergistic anti-tumor effect, which can reduce side effects while increasing drug efficacy.
[0020] 2. The present invention utilizes micelle system to help poorly soluble anti-tumor prodrugs penetrate;
[0021] 3. In the anti-tumor process of the present invention, low molecular weight protamine and polyarginine have a strong transmembrane effect, which can penetrate the tumor surface and reach the deep part, thus avoiding the problem of incomplete tumor chemotherapy and achieving the effect of deep drug delivery in the tumor. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the TF H NMR spectrum in Example 1 of the present invention.
[0023] Figure 2 This is the TF-TA H NMR spectrum in Example 1 of the present invention.
[0024] Figure 3 This is the TF-TA-OH H NMR spectrum in Example 1 of the present invention.
[0025] Figure 4This is the PPa H NMR spectrum in Example 1 of the present invention.
[0026] Figure 5 This is the hydrogen nuclear magnetic resonance spectrum of TF-TA-PPa in Example 1 of the present invention.
[0027] Figure 6 LC-MS chart of Example 1 of the present invention: (A) TF-OH; (B) TF-TA; (C) TF-TA-OH; (D) TF-TA-PPa.
[0028] Figure 7 This is the infrared spectrum of the reactants and products for synthesizing TF-TA-PPa in Example 1 of the present invention.
[0029] Figure 8 It is the differential scanning spectrum of TF (A), PPa (B), the physical mixture of TF and PPa (C), and TF-TA-PPa (D) in Example 1 of the present invention.
[0030] Fig. 9 It is the UV scanning spectrum of TF, TF-TA, TF-TA-OH and TF-TA-PPa in Example 1 of the present invention.
[0031] Fig.10 Full wavelength fluorescence scan of DMSO, PPa and TF-TA-PPa in Example 1 of the present invention. (A) is the emission spectrum under fixed excitation of 510 nm; (B) is the excitation spectrum under fixed emission of 676 nm.
[0032] Fig.11 The active oxygen generation of PPa and TF-TA-PPa in Example 1 of the present invention.
[0033] Fig.12 This is an appearance diagram of the TF-TA-PPa-PMs solution and TF-TA-PPa suspension in Example 2 of the present invention.
[0034] Fig.13 This is the particle size distribution diagram of TF-TA-PPa-PMs in Example 2 of the present invention.
[0035] Fig.14 The infrared spectra of Example 2 of the present invention are (A) Poloxamer 188; (B) blank micelles; (C) TF-TA-PPa; (D) TF-TA-PPa-PMs.
[0036] Fig.15 This is a transmission electron microscopy image of TF-TA-PPa-PMs (×60.0k) in Example 2 of the present invention.
[0037] Fig.16These are the results of the inter-group difference analysis between the drug-loaded microneedles in Example 3 of the present invention.
[0038] Fig.17 This is the gross appearance of MNs-TF-TA-PPa-PMs and MNs-PMs in Example 3 of the present invention and the needle bodies of MNs-TF-TA-PPa-PMs and MNs-PMs under an optical microscope.
[0039] Fig.18 This is a scanning electron microscope image of MNs-TF-TA-PPa-PMs in Example 3 of the present invention.
[0040] Fig.19 This is a fluorescence microscope image of MNs-TF-TA-PPa-PMs in Example 3 of the present invention.
[0041] Fig. 20 This is the compression-stress curve of MNs-TF-TA-PPa-PMs in Example 3 of the present invention (n=3).
[0042] Fig.21 This is the result of the morphology of the needle holes on the skin after microneedle puncture in Example 3 of the present invention.
[0043] Fig. 22 This is a tissue section diagram after the microneedles in Example 3 of the present invention penetrated into the back skin of a rat.
[0044] Fig.23 This is the change in needle tip morphology after MNs-TF-TA-PPa-PMs in Example 3 of the present invention punctures the skin.
[0045] Fig.24 This is the recovery of the skin in Example 3 of the present invention 24 hours after microneedle puncture.
[0046] Fig.25 This is an investigation on the hygroscopicity of the microneedles in Example 3 of the present invention (n=3).
[0047] Fig.26 This is the DSC thermal analysis of the microneedles in Example 3 of the present invention.
[0048] Fig. 27 This is the infrared spectrum of the microneedle in Example 3 of the present invention.
[0049] Fig.28 The generation of reactive oxygen species in MNs-PPa-PMs and MNs-TF-TA-PPa-PMs.
[0050] Fig.29 This is the standard curve of drug loading of soluble microneedles in Example 3 of the present invention.
[0051] Fig.30HPLC chromatograms of Example 3 of the present invention: (A) TF-OH; (B) blank microneedle; (C) TF-TA-PPa loaded microneedle. DETAILED DESCRIPTION
[0052] The technical solution of the present invention is further illustrated and described below through specific implementation modes in combination with the accompanying drawings.
[0053] Example 1: Synthesis and characterization of TF-TA-PPa conjugate
[0054] 1 Synthesis of TF-TA-PPa conjugate
[0055] The synthetic route of TF-TA-PPa conjugate is shown below.
[0056]
[0057] The specific steps include:
[0058] (1) Synthesis of TF hydroxylated derivative (TF-OH): Weigh 2.0 g of TF and dissolve it in 10 mL of formaldehyde. The mixture was stirred under magnetic stirring at 60°C for 6 h and monitored by thin layer chromatography (TLC). After the reaction of the raw materials was complete, 2 to 3 times the amount of methanol in the reaction solution was added and the water was removed by rotary evaporation to obtain TF-OH.
[0059] (2) Synthesis of TF-thioglycolic anhydride derivative (TF-TA): Weigh 3.9 g of thioglycolic anhydride (TA) and dissolve it in 10 mL of tetrahydrofuran (THF), add it dropwise to TF-OH, add 10 mL of THF, stir the mixture under magnetic stirring at 35°C for 10 min, add 4.2 mL of triethylamine, stir the mixture under magnetic stirring at 35°C for 24 h, monitor by TLC, and the reaction of the raw material is complete to obtain a crude product of TF-TA. Purify TF-TA by 300-400 mesh silica gel column chromatography, with the mobile phase ratio of methanol: dichloromethane (DCM) = 1:80.
[0060] (3) Synthesis of TF-TA hydroxylated derivative (TF-TA-OH): Weigh 0.4 g of 4-dimethylaminopyridine (DMAP) and 1.7 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC·HCl), dissolve pure TF-TA in 3 mL of DCM, add EDC·HCl, DMAP and 15 mL of ethylene glycol (EG), and react at 35°C with magnetic stirring for 24 h. Monitor by TLC. After the reaction of the raw materials is complete, extract three times with saturated brine:DCM (1:1), remove the organic solvent by rotary evaporation, and chromatograph on a 300-400 mesh silica gel column with a mobile phase ratio of methanol:DCM = 1:50 to obtain pure TF-TA-OH.
[0061] (4) Synthesis of TF-TA-PPa conjugate: Weigh 0.07 g PPa, 0.08 g EDC·HCl, and 0.018 g DMAP, dissolve pure TF-TA-OH in 5 mL DCM, then add weighed PPa, EDC·HCl, and DMAP, react for 24 h at 35°C in the dark, and separate TF-TA-PPa with 300-400 mesh silica gel, and the mobile phase ratio is methanol: DCM = 1:100. Collect the target product, remove the excess organic solvent by rotary evaporation, and then separate and purify TF-TA-PPa by preparative liquid chromatography, and the mobile phase ratio is 100% methanol, flow rate: 15 mL / min, column: Sunfire C18 5μm, 19mm×250mm, wavelength: 271nm, 408nm.
[0062] 2 Structural characterization and in vitro properties of TF-TA-PPa conjugates
[0063] 2.1 Structural characterization of TF-TA-PPa conjugate
[0064] H NMR ( 1 H-NMR): About 5 mg of TF, TF-TA, TF-TA-OH, PPa, and TF-TA-PPa were respectively weighed and dissolved in a mixed solvent of dimethyl sulfoxide (DMSO) for H-NMR spectrum measurement.
[0065] Liquid chromatography-mass spectrometry (LC-MS): TF-OH, TF-TA, TF-TA-OH, and TF-TA-PPa were dissolved in methanol to prepare a 20 μg / mL solution for mass spectrometry verification samples.
[0066] Fourier transform infrared spectroscopy (FT-IR): Take an appropriate amount of fully dried potassium bromide and TF, PPa, TF-TA-PPa, mix them thoroughly in an agate mortar, grind them, and press them into tablets. Measure the -1 Infrared absorption in the range.
[0067] 2.2 In vitro properties of TF-TA-PPa conjugates
[0068] Differential Scanning Calorimetry (DSC): Weigh appropriate amounts of TF, PPa, physical mixture of TF and PPa, and TF-TA-PPa powder respectively, place them in an aluminum crucible, spread them flat on the bottom of the crucible, use a blank crucible as a control, and use nitrogen as a purge gas and protective gas. Set the heating rate to 10°C / min, heat from 30°C to 280°C, perform DSC analysis, and determine the melting point.
[0069] UV spectral scanning: Weigh appropriate amounts of TF, TF-TA, TF-TA-OH, and TF-TA-PPa into a 100 mL volumetric flask, dissolve them in methanol, and dilute to the mark to prepare a 20 μg / mL solution. Measure the full-wavelength absorption scan at 200-800 nm with a UV spectrophotometer.
[0070] Fluorescence spectrum scanning: Accurately weigh equimolar amounts of PPa (5.3 mg) and TF-TA-PPa (9.2 mg), respectively, and place them in 10 mL volumetric flasks, dissolve them with DMSO and dilute to the mark, prepare a stock solution with a concentration of 1 mM, and then dilute them with the stock solution to make a 10 μM working solution. Take 200 μL and place it in a black 96-well fluorescent plate, and use a multifunctional microplate reader to perform fluorescence spectrum scanning. The scanning modes are fixed excitation wavelength of 510 nm, scanning its fluorescence emission spectrum in the range of 600-800 nm; fixed emission wavelength of 673 nm, scanning its fluorescence excitation spectrum in the range of 450-600 nm.
[0071] 2.3 Determination of reactive oxygen species under laser irradiation
[0072] DCFH-DA (Dichlorofluorescein Diacetate, 2',7'-dichlorofluorescein diacetate) is an indicative probe that has no fluorescence itself and can freely pass through the cell membrane. After being oxidized by ROS, its metabolite DCFH can generate DCF with fluorescent properties, which emits green fluorescence after excitation. The intensity of the green fluorescence is proportional to the level of reactive oxygen. Therefore, the DCFH-DA fluorescent probe method is used to measure reactive oxygen.
[0073] Use a pipette to draw 10μL of 10.0mM DCFH-DA solution and dilute it to 1.0mM DCFH-DA as a stock solution. Accurately weigh 0.008g of sodium hydroxide (NaOH) and dissolve it in 20mL of deionized water to prepare a 10mM NaOH stock solution. Accurately weigh 0.335g of disodium hydrogen phosphate (NaH2PO4), add deionized water to 100mL, completely dissolve it, and prepare a 25mM NaH2PO4 buffer. Take 0.1mL of the prepared DCFH-DA stock solution, mix it with 0.4mL of NaOH stock solution, incubate it at room temperature for 1h to completely hydrolyze it, then take NaH2PO4 buffer to neutralize it to pH 7.0 to obtain DCFH solution, and store it in a 4℃ refrigerator for later use.
[0074] Preparation of sample solution: Accurately weigh equimolar amounts of PPa (5.3 mg) and TF-TA-PPa (9.2 mg), place them in 10 mL volumetric flasks, dissolve them in DMSO and dilute to the mark to prepare a stock solution with a concentration of 1 mM; take 0.5 mL of PPa stock solution and TF-TA-PPa stock solution, dilute to 1 L with water to prepare a solution with a concentration of 0.5 μM. Take 200 μL of the prepared PPa solution and TF-TA-PPa solution, add them to a black 96-well plate, and add 10 μL of DCFH solution to each well. Under laser irradiation (1 W / cm 2 )0s, 30s, 60s, 90s, 120s, 150s, 300s and 480s later, the fluorescence intensity under excitation at 488nm and emission at 525nm was measured respectively.
[0075] 3 Results and discussion
[0076] 3.1 Characterization by H NMR
[0077] Figures 1 to 5 The following are the hydrogen NMR spectra of TF, TF-TA, TF-TA-OH, PPa, and TF-TA-PPa conjugates. Under 60°C, the secondary amine in the TF structure and formaldehyde react through the Eschweiler-Clarke reaction to form TF-OH with -OH at the end so that the next reaction can proceed. TA undergoes ring-opening esterification and reacts with -OH to form an ester bond, thereby exposing the -COOH end. Figure 1 , Figure 2 As shown, after TF is connected to TA through esterification reaction, 1The H-NMR spectrum showed a new -COOH signal peak at 12.65ppm, a new -CH2- signal peak replacing the secondary amine hydrogen appeared at 5.83ppm, and -CH2- signal peaks No. 20 and No. 18 appeared at 3.46ppm and 3.33ppm, respectively. In addition, the secondary amine signal peak of TF at 11.75ppm disappeared, indicating that formaldehyde was connected to the secondary amine bond and -OH was produced, which was then connected to -OH through TA ring opening to generate TF-TA with -COOH at the end and a thioether bond.
[0078] TF NMR assignments are as follows: 1 H-NMR (400MHz, DMSO-d6, δ): 11.75 (s, 1H, NH), 7.85 (d, 1H, CH), 5.89 (m, 1H, CH), 4.22 (m, 1H, CH2), 3.80 (m, 1H, CH2), 2.21 (m, 1H, CH2), 1.93 (m, 1H, CH2).
[0079] TF-TA NMR assignments are as follows: 1 H-NMR (400MHz, DMSO-d6, δ): 12.65 (s, 1H, COOH), 8.03 (d, 1H, C=CH), 5.94 (ddd, 1H, OCH), 5.83 (q, 2H, CH2), 4.26 (q, 2 H, CH2), 3.83 (q, 2H, CH2), 3.46 (s, 2H, CH2), 3.37 (s, 2H, CH2), 2.24 (m, 1H, CH2), 2.06 (m, 2H, CH2), 1.92 (m, 2H, CH2).
[0080] The terminal carboxyl group of TF-TA is esterified by EDC·HCl and DMAP to become an active ester, and then the hydroxyl group of EG and the active ester are transesterified to connect EG and TF-TA to form TF-TA-OH with -OH at the terminal. Figure 3 As shown in the figure, the -COOH signal peak of TF-TA at 12.65ppm disappeared, the -OH signal peak appeared at 4.80ppm, and the 25th and 26th hydrogen signal peaks on EG appeared at 3.56ppm and 4.05ppm, indicating that the esterification of EG and TF-TA was successful.
[0081] TF-TA-OH NMR assignments are as follows: 1H-NMR (400MHz, DMSO-d6, δ): 8.03 (d, 1H, C=CH), 5.94 (ddd, 1H, CH), 5.83 (q, 2H, CH2), 4.80 (t, 1H, OH), 4.26 (q, 1H, CH2), 4.05 (q, 2H, CH2), 3.83 (q, 1H, CH2), 3.56 (q, 2H, CH2), 3.50 (s, 2H, CH2), 3.47 (s, 2H, CH2), 2.25 (m, 1H, CH2), 2.04 (m, 1H, CH2), 1.93 (m, 2H, CH2).
[0082] Use EDC·HCl and DMAP to activate the terminal carboxyl group of PPa, and then transesterify the terminal hydroxyl group of TF-TA-OH with the active ester to connect PPa. Figure 3 , Figure 4 , Figure 5 As shown, Figure 5 The characteristic peaks of PPa δ9.71ppm, δ9.43ppm, δ8.89ppm and the characteristic peak of TF-TA-OH δ7.90ppm appeared in the aromatic region, and the characteristic peaks of PPa δ3.60ppm, δ3.21ppm and the characteristic peaks of TF-TA-OH δ1.90ppm, δ1.77ppm appeared in the fat region, and their integrals corresponded. The characteristic peaks of PPa δ2.40ppm, δ0.23ppm and the characteristic peaks of TF-TA-OH δ4.58ppm, δ4.33ppm existed in the spectrum, indicating that TF-TA-PPa was successfully synthesized.
[0083] The NMR assignments of PPa are as follows: 1 H NMR (400MHz, DMSO-d6) δ: 9.62 (d, 1H, C=CH), 9.36 (d, 1H, C=CH), 8.88 (d, 2H, NH), 8.19 (t, 1H, C=CH), 6.34 (t, 1H, C=CH), 6.18 (t, 2H, CH2), 5.25-5.06 (m, 2H, CH2), 4.57 (s, 1H, CH), 4.30 (s, 1H, CH), 3.56 (t, 3H, CH3), 3.16 (d, 3H, CH3), 2.62-2.53 (m, 2H, CH2), 2.36-2.28 ( m, 2H, CH2), 2.12-2.04 (m, 3H, CH3), 1.77 (d, 3H, CH3), 1.58 (q, 3H, CH3), 0.14 (d, 2H, CH2).
[0084] The NMR assignments of TF-TA-PPa are as follows: 1H NMR (400MHz, DMSO-d6) δ: 9.71 (d, 1H, PPa), 9.43 (d, 2H, PPa), 8.89 (s, 1H, PPa), 8.26-8.16 (m, 1H, PPa), 7.94-7.84 (m, 1H, TF), 6 .38(d,1H,PPa),6.21(d,2H,PPa),5.75(s,1H,TF),5.75(s,1H,TF),5.52(q,2H,PPa),5.25-5.08(m,1H,TF),4.58(d,2H,TF),4 .33 (d, 2H, TF), 4.24-4.12 (m, 2H, PPa), 3.69 (d, 2H, TF), 3.60 (s, 3H, PPa), 3.43 (s, 4H, TF), 3.29 (d, 1H, PPa), 3.21 (d, 3H, PPa), 2.70-2.61 (m, 2H, PPa), 2.40 (d, 2H, PPa), 2.11 (s, 3H, TF), 1.90 (s, 1H, TF), 1.77 (d, 6H, TF), 1.61 (s, 3H, PPa), 0.23 (s, 2H, PPa).
[0085] 3.2 Mass spectrometry characterization
[0086] Figure 6 These are the LC-MS graphs of TA-OH, TF-TA, TF-TA-OH, and TF-TA-PPa. Figure 6 As shown, A is TF-OH, LC-MS m / z for C9H 11 FN2O4[M+Na] + calcd 229.95, found 252.95, consistent with the theoretical molecular weight of 230.07; B is TF-TA, LC-MS m / z for C 13 H 15 FN2O7S[MH] - calcd 362.00, found 361.00, consistent with the theoretical molecular weight of 362.06; C is TF-TA-OH, LC-MS m / z for C 15 H 19 FN2O8S[M+H] + calcd406.05, found407.05, consistent with the theoretical molecular weight 406.08; D is TF-TA-PPa, LC-MS m / z for C 48 H 51 F6O 10 S[M+H] +Calcd 922.35, found 923.35, consistent with the theoretical molecular weight 922.34.
[0087] 3.3 Fourier-infrared spectroscopy characterization
[0088] Figure 7 The infrared spectra of TF, PPa, and TF-TA-PPa are shown in Figure 1. -1 The peak at 1714 cm is caused by C=C stretching vibration. -1 The peak at 3168 cm is the stretching vibration peak of -C=O of TF. -1 The peaks appearing at 1674 cm-1 are the stretching vibration peaks caused by -NH. The infrared spectrum of PPa shows that the stretching vibration peaks caused by the carbon-carbon double bond and keto group of PPa appear at 1674 cm-1, - 1. 1726cm -1 , at 3093cm -1 The broad peak at 3394 cm is the stretching vibration caused by -NH. The shift may be due to the hydrogen bond between -NH and the adjacent N. -1 The peak is caused by the stretching vibration of -OH on the carboxyl group of PPa; the infrared spectrum of TF-TA-PPa shows that at 3091cm -1 The peak that appears corresponds to the peak produced by the -NH stretching vibration on PPa, 1735cm -1 It is the stretching vibration caused by the ester bond, which is the ester bond formed by the connection between the carboxyl group of PPa and TF-TA-OH, 1689cm -1 The peak at 2869cm is caused by the stretching vibration of C=C on TF and PPa. -1 、2960cm -1 The peak at is caused by the stretching vibration of the methyl and methylene groups on TF and PPa, indicating that the synthesis of TF-TA-PPa was successful.
[0089] 3.4 Differential Scanning Calorimetry Characterization
[0090] Figure 8 It is the differential scanning spectrum of TF, PPa, the physical mixture of TF and PPa, and TF-TA-PPa. As can be seen from the figure, TF has an endothermic peak at 180℃ and an exothermic peak at 220℃; PPa has an exothermic peak at 251℃; the endothermic peak of the physical mixture of TF and PPa is reduced to 176℃, and the exothermic peak is reduced to 220℃; the endothermic peak of TF-TA-PPa changes significantly, with an endothermic peak at 76℃~94℃, showing a bimodal distribution, proving that TF-TA-PPa is a synthetic new substance prodrug.
[0091] 3.5 UV spectrum scanning
[0092] Fig. 9 This is the UV scanning spectrum of TF, TF-TA, TF-TA-OH, and TF-TA-PPa. According to the UV spectrum, the UV maximum absorption wavelength of TF is located at 269nm, and the UV maximum absorption wavelengths of TF-TA and TF-TA-OH are also located at 269nm. Similarly, TF-TA-PPa also has an absorption wavelength at 269nm; in addition to absorption at 269nm, TF-TA-PPa has a UV maximum absorption wavelength at 407nm, which is caused by the conjugation effect of the porphyrin ring in its structure.
[0093] 3.6 Fluorescence spectroscopy scanning
[0094] Fig.10 It is the fluorescence spectra of DMSO, PPa, and TF-TA-PPa. Fig.10 As shown in (A), PPa has maximum fluorescence emission at 676nm and weak emission at 724nm under 510nm excitation, while the emission wavelength of the derivative TF-TA-PPa obtained by denaturing the carboxyl end of PPa has not been changed. Fig.10 As shown in (B), at a fixed emission of 676 nm, PPa and TF-TA-PPa each have a strong excitation at 510 nm and 540 nm, which shows that the excitation wavelength of PPa has not changed after the -COOH modification. Comparing the fluorescence intensity of PPa and TF-TA-PPa, at the same PPa concentration, the fluorescence intensity of TF-TA-PPa is weakened, which may be due to the rigid coplanar structure of TF-TA-PPa structure affected by -COOH denaturation.
[0095] 3.7 Determination of reactive oxygen species under laser irradiation
[0096] Fig.11 It is the generation of reactive oxygen species (ROS) of PPa and TF-TA-PPa. As can be seen from the figure, after laser irradiation, under 488nm excitation and 525nm emission, the fluorescence intensity of the PPa group and the TF-TA-PPa group increased with the increase of irradiation time. The fluorescence intensity of the PPa group and the TF-TA-PPa group was almost the same from 0s to 150s, and the difference began to increase after 150s. This may be because the TF-TA-PPa structure contains TF, which is the prodrug form of PPa. TF will form steric hindrance. As time goes by, part of PPa is slowly released to generate ROS.
[0097] Example 2 Preparation and characterization of TF-TA-PPa conjugate micelles
[0098] The TF-TA-PPa conjugate synthesized in Example 1 is a poorly soluble prodrug, and its therapeutic effect is poor due to its poor water solubility. In order to facilitate the preparation of soluble microneedles and improve the water solubility and drug release of drug-loaded microneedles, it is prepared into a micellar solution. F68 is an amphiphilic triblock copolymer with advantages such as good biocompatibility, low toxicity, and good drug solubilization ability, so it is selected as the micelle carrier material in this example.
[0099] In this example, the micellar solution loaded with TF-TA-PPa conjugate, i.e., TF-TA-PPa-PMs, was prepared by solvent evaporation method. The precipitation degree of drug-loaded micelles and their particle size, potential, and PDI were used as indicators. The prescription was optimized through single factor investigation, the optimal prescription was screened out, and the process verification was performed, as follows:
[0100] 1 Experimental methods
[0101] 1.1 Preparation of TF-TA-PPa-PMs
[0102] Micelles were prepared by solvent evaporation method. Appropriate amount of TF-TA-PPa and F68 were dissolved in 2 mL of 60°C anhydrous ethanol, slowly added dropwise to 15 mL of 60°C deionized water under stirring conditions, and stirred at room temperature in the dark for 24 h to obtain TF-TA-PPa-PMs.
[0103] 1.2 Single factor investigation of drug loading ratio
[0104] The drug-carrier ratio (TF-TA-PPa: F68, w / w) was designed to be 1:1, 1:2, 1:3, 1:4, 1:5, and 1:10, respectively. TF-TA-PPa-PMs with different drug-carrier ratios were prepared according to item "1.1". The precipitation, particle size, PDI, and Zeta potential were comprehensive indicators with a full score of 100 points, of which the precipitation degree accounted for 40%, with the minimum value being 40 points; the particle size accounted for 40%, with the maximum value being 40 points; the PDI accounted for 10%, and the Zeta potential accounted for 10%. The particle size, PDI, and Zeta potential of TF-TA-PPa-PMs with different drug-carrier ratios were measured using a Malvern particle size analyzer at 25°C. The experiments were repeated three times in parallel and the average value was taken. The best prescription was selected.
[0105] 1.3 Characterization of TF-TA-PPa-PMs
[0106] 1.3.1 Solubility
[0107] Prepare TF-TA-PPa-PMs according to "1.1" to obtain 10 mL of micellar solution, which is placed in a transparent glass container. Take an appropriate amount of TF-TA-PPa and add 10 mL of deionized water, stir at room temperature for 24 hours to prepare a TF-TA-PPa suspension, which is placed in a transparent glass container. Observe the solubility of TF-TA-PPa and investigate the solubilization effect of TF-TA-PPa-PMs.
[0108] 1.3.2 Particle size and potential verification
[0109] TF-TA-PPa-PMs were prepared according to the optimal formula, and three batches of repeated experiments were carried out. The particle size, PDI and Zeta potential of TF-TA-PPa-PMs with the optimal formula were determined using a Malvern particle size analyzer.
[0110] 1.3.3 Infrared spectroscopy characterization
[0111] Prepare TF-TA-PPa-PMs according to "1.1", take an equal amount of F68 to prepare blank micelles, freeze at -80℃ for more than 4h, and use a freeze dryer to obtain freeze-dried powder. Take an appropriate amount of dry potassium bromide and F68, blank micelle freeze-dried powder, and drug-loaded micelle freeze-dried powder, mix and grind them thoroughly in an agate mortar, and then press them into tablets. Use an infrared spectrometer to measure their infrared spectra at 400-4000cm -1 Infrared absorption in the range.
[0112] 1.3.4 Transmission electron microscopy
[0113] Take 10 μL of TF-TA-PPa-PMs prepared according to the optimal recipe and drop it on the copper grid. After 3 minutes, absorb the excess liquid with filter paper, add 2% phosphotungstic acid solution for negative staining for 30 seconds, dry naturally, and observe the microscopic morphology of TF-TA-PPa-PMs by transmission electron microscope (TEM).
[0114] 2 Results and discussion
[0115] 2.1 Single factor investigation of drug loading ratio
[0116] The results of the single factor investigation of drug loading ratio are shown in Table 3-1. When the drug loading ratio is 1:5, there is no precipitation in the micelle solution, the particle size is small, (113.33±1.61) nm, the PDI is 0.30±0.026, the distribution is relatively uniform, the Zeta potential is (-23.00±0.60) mV, and the comprehensive evaluation is 97%. Therefore, the drug loading ratio of 1:5 is selected as the best prescription.
[0117] Table 2-1 Results of single factor investigation on drug loading ratio ( n=3)
[0118]
[0119]
[0120] + indicates the degree of precipitation; - indicates no precipitation.
[0121] 2.2 Solubility
[0122] Fig.12 The appearance of TF-TA-PPa-PMs solution and TF-TA-PPa suspension, the left side is TF-TA-PPa-PMs solution, the right side is TF-TA-PPa suspension. It can be seen from the figure that: TF-TA-PPa-PMs solution is brown-yellow, clear and transparent with opalescence, and the solution is uniform; TF-TA-PPa is insoluble in aqueous solution, forming small particles that remain at the bottom; this shows that TF-TA-PPa-PMs greatly improves the solubility of poorly soluble drugs.
[0123] 2.3 Particle size and potential verification
[0124] Fig.13 The particle size distribution diagram of TF-TA-PPa-PMs with a drug loading ratio of 1:5. TF-TA-PPa-PMs were prepared with the optimal prescription drug loading ratio of 1:5, and three batches of repeated tests were carried out. The results are shown in Table 2-2. It can be seen that the preparation process of micelle solution with a drug loading ratio of 1:5 is stable and feasible, and the prepared micelle particle size is more suitable.
[0125] Table 2-2 Prescription process verification results ( n=3)
[0126]
[0127] 2.4 Infrared spectroscopy characterization
[0128] Fig.14 The infrared spectra of F68, blank micelles containing only F68, TF-TA-PPa, and TF-TA-PPa-PMs are shown in Figure 2. -1 The peak at 2850 cm corresponds to the -OH stretching vibration peak on F68. -1 The peak at 1375 cm corresponds to the stretching vibration peak of -CH2- on F68. -1 The peak at 1110 cm corresponds to the -CH3 stretching vibration peak on F68. -1 and 1056cm -1 The -CO stretching vibration peak at is a characteristic peak of F68. Due to the micelle wrapping, it can be clearly seen that the peak intensity of F68 in the infrared spectrum of blank micelles (B) is weaker than that in the infrared spectrum of F68 (A).
[0129] The infrared spectrum of TF-TA-PPa shows that at 3078 cm -1 The peak at 1689cm is caused by the -NH on TF-TA-PPa and is a characteristic peak of TF-TA-PPa. -1 The peak at 1735 cm is caused by the stretching vibration of the carbon-carbon double bond. -1 The peak formed is the characteristic peak of the ester bond of TF-TA-PPa. Compared with the infrared spectrum of TF-TA-PPa-PMs, the peak at 2889 cm -1 、1110cm -1 、1058cm -1 The peak at 1732cm is the characteristic peak of F68. -1 、1689cm -1 The peak at is the characteristic peak of TF-TA-PPa, but due to the formation of micelles, its peak is not obvious. As can be seen from the figure, the drug-loaded micelles successfully loaded TF-TA-PPa.
[0130] 2.5 Transmission electron microscopy
[0131] Fig.15 Figure 1 is a transmission electron microscope image of TF-TA-PPa-PMs. Fig.15 It can be seen that TF-TA-PPa-PMs are nearly spherical, with a particle size of about 100 nm, relatively uniform distribution, regular morphology, and stable micelles.
[0132] Example 3 Preparation and characterization of soluble microneedle preparation of TF-TA-PPa-PMs
[0133] 1 Experimental methods
[0134] 1.1 Preparation of microneedles
[0135] Microneedles were prepared by centrifugation as follows: appropriate amounts of PSF, Arg8, and PVP-K90 were weighed and dissolved in 5 mL of the TF-TA-PPa conjugate micelle solution prepared in Example 2, stirred, and swollen to obtain a microneedle matrix solution, and about 0.4 mL was added to an 800 μm microneedle mold, centrifuged at 5000 rpm / min for 5 min, centrifuged twice to allow the microneedle matrix solution to fully enter the mold, placed in a 45°C oven to dry in the dark for 6 h, and finally demolded, and the successfully prepared microneedles were placed in a desiccator and stored in the dark. Microneedle MNs-TF-TA-PPa-PMs loaded with TF-TA-PPa-PMs were obtained.
[0136] 1.2 Matrix ratio screening
[0137] Different ratios of PSF and PVP-K90 were designed, and Arg8 was taken as 5% of the total mass of the first two. MNs-TF-TA-PPa-PMs and blank microneedles without drug loading (MNs-PMs) were prepared according to item "1.1". The mass ratios of PSF:PVP-K90 of 1:9, 1.5:8.5, and 2:8 were investigated, and three parallel experiments were conducted. The formability, demoulding difficulty, and mechanical strength of the microneedle patch were used as indicators to select the best prescription.
[0138] 1.3 Characterization of MNs-TF-TA-PPa-PMs
[0139] 1.3.1 Morphological investigation
[0140] Take the best prescription microneedle material and prepare MNs-TF-TA-PPa-PMs according to item "1.1". Fix the needle tip on a horizontal plane with the needle tip facing upward, observe the overall morphology of the microneedle and take a picture. Tilt the needle tip 45° and fix it on the table. Use an optical microscope to observe and take a picture of the microneedle.
[0141] Take the best prescription microneedle material and prepare MNs-TF-TA-PPa-PMs according to item "1.1". Fix the needle tip with the tip facing up on a 45° inclined metal stand, then spray gold for about 30 seconds, and use a scanning electron microscope (SEM) to further observe the microneedle.
[0142] Take the best prescription microneedle material and prepare MNs-TF-TA-PPa-PMs according to item "1.1". Since TF-TA-PPa itself has fluorescent properties, MNs-TF-TA-PPa-PMs have fluorescent properties. Cut MNs-TF-TA-PPa-PMs into strips along the array and observe the distribution state of TF-TA-PPa under a fluorescence microscope.
[0143] 1.3.2 Mechanical strength
[0144] Take the best prescription microneedle material, prepare MNs-TF-TA-PPa-PMs according to item "1.1", cut the prepared microneedles into 5×5 microneedle arrays, fix them on a glass slide with the needle tip facing up, place the glass slide on the measuring table of the texture analyzer, select the P50 probe during the test, set the compression mode, set the rate parameters: pre-test rate 1.00 mm·s -1 , measuring speed 0.01mm·s -1 , after measuring speed 10mm·s -1 ; The target mode selects displacement, displacement 0.800mm; the trigger mode is automatic (force); the trigger force is 0.049N, and the stress on the microneedle tip during the displacement of the probe is measured to obtain the mechanical strength of the microneedle tip.
[0145] In vitro experiment: Take the best prescription microneedle material, prepare the microneedle matrix solution according to the method under "1.1", add 2mL of trypan blue to the microneedle matrix solution, stir evenly, and prepare trypan blue-stained MNs-TF-TA-PPa-PMs. Healthy SD rats were killed by cervical dislocation, the hair on the back of the rats was shaved and depilated, and the rats were cleaned with saline. The back skin was cut and then laid flat on a clean table with the stratum corneum facing down. The subcutaneous fat tissue and connective tissue were peeled off, and the surface moisture was wiped dry. MNs-TF-TA-PPa-PMs and trypan blue-stained MNs-TF-TA-PPa-PMs were pressed with the thumb to puncture the treated rat back skin, and removed after 20 minutes. The pore morphology of the skin after microneedle puncture was observed and photographed.
[0146] In vivo experiment: Take the best prescription microneedle material, prepare the microneedle matrix solution according to the method under "1.1", add 2 mg of rhodamine B to the microneedle matrix solution, stir evenly, and prepare rhodamine B-stained MNs-TF-TA-PPa-PMs. Shave the back hair of living healthy SD rats, apply depilatory cream to remove hair, and then wash with saline. Apply rhodamine B-stained MNs-TF-TA-PPa-PMs to the back skin of rats for 5 minutes, remove the microneedles, observe the pore morphology of the skin after microneedle puncture, and take pictures.
[0147] 1.3.3 Puncture depth
[0148] The best prescription microneedle material was taken, and MNs-TF-TA-PPa-PMs were prepared according to item "1.1". They were attached to the back skin of SD rats after depilation, and the skin was pressed for 3 minutes before removal, and the corresponding area was marked. The rats were killed by dislocation, and the back skin was removed. The skin was then fixed in 4% paraformaldehyde solution, cryosectioned, stained with hematoxylin-eosin (H&E), and analyzed using a digital slice automatic scanning platform.
[0149] 1.3.4 Solubility evaluation
[0150] Clean, depilated SD rat back skin was obtained and divided into areas. The prepared dry MNs-TF-TA-PPa-PMs were pressed on the skin with the thumb for 1, 5, 10, 15, 20, 25, 35, 45, and 55 min, respectively. The microneedles were then peeled off and dried in a 45°C oven for 6 h. The length and morphological changes of the microneedle tips were observed using an optical microscope.
[0151] 1.3.5 Biocompatibility test
[0152] The prepared dried MNs-TF-TA-PPa-PMs were applied to the back skin of depilated SD rats for 3 minutes, then the microneedles were removed and the area was marked. After 24 hours, the area was cut and fixed in a 4% paraformaldehyde solution. Low-temperature frozen sections were performed, H&E staining was performed, and analysis was performed using a digital section automatic scanning platform. The skin recovery was recorded, and skin irritation and biocompatibility were investigated.
[0153] 1.3.6 Moisture absorption rate
[0154] Using blank microneedle MNs-PMs as a control, weigh the MNs-TF-TA-PPa-PMs that had been dried for 48 hours, then place them in a watch glass and put them into a sealed container together with a beaker filled with 50 mL of saturated saline (relative humidity of saturated saline: 75%). Weigh them at 0, 3, 6, 9, 12, and 24 hours, perform three parallel experiments, and calculate the moisture absorption rate according to formula 3-1.
[0155] Moisture absorption rate (W) (%) = (m i -m0) / m0 (3-1)
[0156] In formula 3-1, m0 represents the mass of the microneedle before measurement, m i Represents the microneedle mass at different time points.
[0157] 1.3.7 Differential Scanning Calorimetry Characterization
[0158] Take a piece of drug-loaded microneedle and a piece of blank microneedle respectively, cut them into pieces with scissors, and grind them in a mortar. Because the microneedles are very tough, they can only be ground into small fragments. Weigh appropriate amounts of drug-loaded microneedle small fragments, blank microneedle small fragments, PSF, Arg8, PVP-K90, and TF-TA-PPa respectively and place them in an aluminum crucible, with an empty crucible as a control. At the same time, use nitrogen as the purge gas and protective gas, set the heating rate to 10℃ / min, heat from 30℃ to 280℃, and perform DSC scanning.
[0159] 1.3.8 Infrared spectroscopy characterization
[0160] Since the drug-loaded microneedles and blank microneedles are very tough, and PVP-K90 and Arg8 are crystalline and cannot be ground into powder, appropriate amounts of drug-loaded microneedle fragments, blank microneedle fragments, and PVP-K90 are put into an EP tube, dissolved in 2 mL of anhydrous ethanol, and set aside.
[0161] Weigh appropriate amounts of dried potassium bromide, TF-TA-PPa, and PSF, mix and grind them in an agate mortar until the particle size is about 5 μm, and then press them into tablets. Use an infrared spectrometer at 400-4000 cm -1 Scan within range.
[0162] Weigh an appropriate amount of dried potassium bromide and grind it to a particle size of about 5 μm. Then, add 2 drops of drug-loaded microneedle solution, blank microneedle solution, PVP-K90 solution, and Arg8 solution to potassium bromide, dry them under an infrared lamp, press them into tablets, and use an infrared spectrometer at 400-4000 cm -1 Scan within range.
[0163] 1.4 Determination of reactive oxygen species under laser irradiation
[0164] According to the method in "1.1", PPa was loaded into the microneedles (MNs-PPa-PMs). According to the method in "1.3" of Chapter 1, 200 μL of the prepared MNs-PPa-PMs solution and MNs-TF-TA-PPa-PMs solution were added to a black 96-well plate, and 10 μL of DCFH solution was added to each well. The plate was then irradiated with laser (1 W / cm 2 ) After 0, 30, 60, 90, 120, 150, 300 and 480 s, the fluorescence intensity under excitation at 488 nm and emission at 525 nm was measured respectively.
[0165] 1.5 Drug loading
[0166] 1.5.1 Chromatographic conditions
[0167] Chromatographic column: C18 column (4.6×250mm, 5μm, WendaSil TM );
[0168] Mobile phase: methanol: acetonitrile: water (10:5:85);
[0169] Detection wavelength: 271nm;
[0170] Flow rate: 1 mL / min;
[0171] Column temperature: 35 °C;
[0172] Injection volume: 20 μL;
[0173] The number of theoretical plates calculated based on the TF-OH peak is not less than 4000, and the resolution is greater than 1.5.
[0174] 1.5.2 Establishment of standard curve
[0175] Accurately weigh TF-OH and use methanol as solvent to prepare a 2 mg / mL stock solution as the reference solution. Dilute the solution to 0.1, 0.2, 0.5, 1, 2, and 5 μg / mL, respectively. Perform chromatographic detection and establish a curve with the injection concentration (X) as the horizontal axis and the peak area (Y) as the vertical axis. The obtained regression equation is the standard curve equation.
[0176] 1.5.3 Exclusivity
[0177] Prepare a certain concentration of TF-OH according to the method under "1.5.2"; dissolve the TF-TA-PPa-loaded microneedles and blank microneedles in methanol, perform acid destruction and alkali neutralization treatment to prepare a microneedle solution of a certain concentration; pass these four solutions through a 0.22μm microporous filter membrane, inject and analyze, and record the chromatogram.
[0178] 1.5.4 Calculation of drug loading
[0179] Because TF-TA-PPa contains an ester bond and is easily decomposed, acid destruction was used to break the ester bond and expose TF-OH. TF-OH was used as a reference substance to establish a standard curve to determine the drug loading amount.
[0180] Take the best prescription microneedle material and prepare MNs-TF-TA-PPa-PMs according to the method under "1.1". Take the drug-containing microneedle and add 5mL methanol to ultrasonicate to dissolve it completely, add 1mol / L dilute hydrochloric acid for acid destruction, ultrasonicate for 15min, stir for 24h, then neutralize with 1mol / L NaOH, and finally dilute to 100mL with deionized water. Filter 1.5mL with a 0.22μm filter membrane and inject chromatographically. Perform three parallel experiments and calculate the drug loading (Drug loading, DL). The formula for drug loading is as follows:
[0181]
[0182] In formula 3-2, m0 represents the total weight of microneedles. is the amount of TF-TA-PPa calculated from TF-OH, that is, the drug content in each microneedle.
[0183] 2 Results and discussion
[0184] 2.1 Matrix ratio screening
[0185] Table 3-1 shows the results of the single factor investigation of the microneedle matrix ratio. It can be seen from the table that when the microneedle matrix ratio is 1:9, the microneedle has the best formability, good demolding, and the mechanical strength of each needle tip is the strongest; compared with the drug-loaded microneedles and the non-drug-loaded microneedles, the mechanical strength of each ratio is different, indicating that the drug loading has an effect on the strength of the microneedle. This is because the drug TF-TA-PPa loaded by the microneedle has a certain crystal form, which interacts with the spatial structure of the microneedle material, thereby changing the performance of the microneedle.
[0186] Fig.16 The results of the intergroup difference analysis between drug-loaded microneedles are shown in Table 1. There is no significant difference between 1:9 and 1.5:8.5, but there is a significant difference between 1:9 and 2:8. Considering the formability and demolding, the ratio of PSF:PVP-K90=1:9 was selected as the best prescription after comprehensive evaluation.
[0187] Table 3-1 Single factor investigation results of microneedle matrix ratio ( n=3)
[0188]
[0189] + indicates satisfaction; √ indicates pass.
[0190] 2.2 Morphological investigation
[0191] The prepared microneedle array is circular with a diameter of 17.5 mm, the number of microneedle tips is 385, the tip distance is 650 μm, and the tip height is 800 μm. Fig.17 Shown are the gross appearance of MNs-TF-TA-PPa-PMs and MNs-PMs and the needle bodies of MNs-TF-TA-PPa-PMs and MNs-PMs under an optical microscope. Fig.17 (A) Fig.17 (B) is the general view of MNs-TF-TA-PPa-PMs, which is gray-brown in color, with the microneedle tips arranged neatly without broken needles; Fig.17 (C) Fig.17 (D) is the general view of MNs-PMs, which are light yellow in color, with neatly arranged microneedle tips, no broken needles, and no bubbles; Fig.17 (E) The needle body of MNs-TF-TA-PPa-PMs under an optical microscope. The needle tip is conical and the needle shape is complete. The brown drug contained in the microneedle can be seen; Fig.17 (F) shows the needle body of MNs-PMs under an optical microscope. The needle tip is conical, the needle shape is complete, and there is no brown drug. Fig.17 As shown, the microneedles fully fill the microneedle mold without bubbles or depressions at the bottom, and a microneedle array with sharp tips and uniform distribution is formed.
[0192] Fig.18 The middle picture (A) is the SEM of the side of the MNs-TF-TA-PPa-PMs needle tip, the picture (B) is the SEM picture of a single MNs-TF-TA-PPa-PMs needle tip, and the picture (C) is the SEM picture of MNs-TF-TA-PPa-PMs. The SEM shows that the microneedle tips are evenly distributed, neatly arranged as a whole, the needle tips are conical, uniform in thickness, and have good morphology.
[0193] Fig.19 This is an image of MNs-TF-TA-PPa-PMs under a fluorescence microscope. According to the preparation method of the drug-loaded microneedle, both the microneedle tip and the backing contain the drug TF-TA-PPa, and TF-TA-PPa with fluorescent properties exhibits extremely strong fluorescence under a fluorescence microscope.
[0194] 2.3 Mechanical strength
[0195] Fig. 20 This is the compression-stress curve of MNs-TF-TA-PPa-PMs (n=3). The relationship between the stress on the microneedle tip during the probe pressing process and the displacement of the probe was measured by the texture analyzer. It can be seen that as the probe moves, the stress gradually increases, and the curve does not show interruption or sudden drop, indicating that the microneedle tip is not broken during the stress process and is in a bent state; the stress on the 5×5 microneedle array is more than 90N, and the average stress on each needle is 3.66±0.06N, which meets the minimum penetration force of 0.06N required for the microneedle to pierce the skin. Fig. 20 It shows that MNs-TF-TA-PPa-PMs can completely pierce the skin, possess good mechanical properties and have excellent toughness.
[0196] Fig.21 It is the result of microneedle puncture on the back skin of rats. Fig.21 (A) is the morphology of the pinholes in the isolated rat back skin after being pierced by MNs-TF-TA-PPa-PMs. Obvious pinholes can be seen; Fig.21 (B) is the staining result of the back skin of an isolated rat after being punctured with microneedles and then stained with trypan blue. The microneedle tip pierces the skin, causing skin cell death, and trypan blue can stain dead cells. A regularly arranged blue pinhole array can be seen on the skin; Fig.21 (C) is the result of skin staining with rhodamine B after microneedle puncture on the back skin of an in vivo rat. Because the back of the in vivo rat is uneven, only partial staining can be seen, but clear pinholes can be seen in the stained part. Fig.21 This indicates that all the needle tips of the microneedles can penetrate the skin of rats and have good mechanical properties.
[0197] 2.4 Puncture depth
[0198] Fig. 22 This is a tissue section after the microneedle was inserted into the back skin of the rat. Fig. 22 As shown, the outermost dark purple part is the stratum corneum, and the lighter part under the stratum corneum is the epidermis. MNs-TF-TA-PPa-PMs successfully pierced the stratum corneum of the skin and entered the epidermis to form a microchannel with a puncture depth of about 600 μm, indicating that the TF-TA-PPa conjugate can enter the subcutaneous tissue through the microchannel to exert its drug effect; the skin puncture ability of the microneedle is qualified.
[0199] 2.5 Solubility evaluation
[0200] Fig.23 The morphology of the needle tip of MNs-TF-TA-PPa-PMs after piercing the skin. According to the dissolution of the microneedle tip, it can be known that the integrated soluble microneedle takes a long time to dissolve and the dissolution rate is slow.
[0201] 2.6 Biocompatibility test
[0202] Fig.24 This is the recovery of the skin 24 hours after microneedle puncture. Fig.24 As shown in the figure, 24 hours later, the stratum corneum of the skin punctured by the microneedle was basically intact, and the skin had completely recovered. Therefore, the prepared MNs-TF-TA-PPa-PMs had good biocompatibility and was non-irritating to the rat skin without obvious damage.
[0203] 2.7 Moisture absorption rate
[0204] Under room temperature with a relative humidity of 75%, the moisture absorption rate of MNs-TF-TA-PPa-PMs was slightly greater than that of MNs-PMs during the same storage time, indicating that the prodrug TF-TA-PPa is easily hydrolyzed and has an impact on the moisture absorption rate of the microneedles.
[0205] 2.8 Differential Scanning Calorimeter
[0206] Fig.26 The differential scanning spectra of PVP-K90, PSF, Arg8, TF-TA-PPa, blank microneedles, and drug-loaded microneedles are shown in Figure 1. As can be seen from the figure, PVP-K90 has an endothermic peak at 80℃~114℃; PSF has an obvious endothermic peak at 130℃~154℃ and an exothermic peak at 180℃~193℃; Arg8 has an endothermic peak at 131℃~150℃ and 223℃~240℃ respectively; TF-TA-PPa has an endothermic peak at 76℃-94℃, showing a bimodal distribution; the endothermic peak of the blank microneedle is not obvious, located at 57℃-65℃ and 96℃~115℃ respectively; the drug-loaded microneedle has an endothermic peak at 74℃~104℃, which is not obvious. Fig.26 This indicates that TF-TA-PPa exists in the microneedles in an amorphous state, probably because the microneedles form a solid-like dispersion, and the presence of the microneedle material inhibits its crystallization, thereby accelerating the dissolution and release of the poorly water-soluble drug.
[0207] 2.9 Infrared Spectroscopy
[0208] Fig. 27 The infrared spectrum of the microneedle is shown in Figure 1. The infrared spectrum of TF-TA-PPa shows that at 3091 cm -1 The peak at 1735 cm is caused by the stretching vibration of -NH. -1 The peak at 1689 cm is the stretching vibration caused by the ester bond. -1 The peak at 2869cm is caused by the stretching vibration of the carbon-carbon double bond. -1 and 2960cm -1 The peaks at 1654cm-1 and 3460cm -1 The peaks at 2950cm-1 are the peaks produced by the stretching vibration of -C=O and -N on the amide, while the peaks at 2950cm-1 are the peaks produced by the stretching vibration of -C=O and -N on the amide, respectively. -1 and 1461cm -1 The peaks appearing at are caused by -CH3 and -CH2- stretching vibrations respectively; the infrared spectrum of PSF shows that the characteristic peak caused by -OH stretching vibration is 3298cm -1 , at 1654cm -1 The peak that appears is the peak generated by -C=C stretching vibration, which appears at 1471cm -1 and 1346cm -1 The peak is caused by the stretching vibration of methylene and methyl groups; the infrared spectrum of Arg8 shows that at 3194cm -1 The peak that appears is the stretching vibration peak of -OH, which is a characteristic peak at 3433cm -1 The peak is the peak produced by -NH and -NH2 stretching vibration, 1681cm -1 It is the stretching vibration peak of -C=O.
[0209] The infrared spectra of each were compared and analyzed. The infrared spectra of drug-loaded microneedles and blank microneedles appeared at 3464 cm -1 The peak at 1658 cm is caused by the stretching vibration of -N on the amide of PVP-K90 or the stretching vibration of -NH and -NH2 on Arg8. -1 and 1654cm -1 It may be the stretching vibration peak caused by -C=O on PVP-K90 and Arg8 or C=C on PSF and TF-TA-PPa. In addition, the peak at 2950cm -1 and 1461cm -1 These are peaks generated by the -CH3 and -CH2 stretching vibrations of PVP K90, but these two peaks are not obvious in the infrared spectrum of the drug-loaded microneedles, which may be due to the interaction between TF-TA-PPa and PVP-K90, PSF, and Arg8.
[0210] 2.10 Determination of active oxygen species under laser irradiation
[0211] Fig.28This is the situation of MNs-PPa-PMs and MNs-TF-TA-PPa-PMs producing reactive oxygen species (ROS) in vitro under laser irradiation. As can be seen from the figure, after PPa and TF-TA-PPa are prepared into micelles and the drug-loaded micelles are loaded into microneedles, the fluorescence intensity tends to be flat from 0s to 90s, and gradually increases from 120s, indicating that the micelle-microneedle system will control the release of drugs. Under certain laser irradiation, the porphyrin structure in the structure will produce reactive oxygen, which will then oxidize the thioether bond by the reactive oxygen, causing the ester bond to break, achieving the purpose of rapid responsive drug release.
[0212] 2.11 Drug loading
[0213] According to the method under "1.5.2", the linear relationship was investigated, with the injection concentration as the horizontal axis (X) and the peak area as the vertical axis (Y), and the regression equation was obtained as Y = 60725X + 1960.3, r 2 =0.9999, the results show that when TF-OH is 0.1μg / mL-5μg / mL, the injection concentration and peak area have a good linear relationship ( Fig.29 ).
[0214] Fig.30 The chromatogram obtained from the specificity test showed that the microneedle excipients had no interference with the determination of TF-OH and had good specificity.
[0215] The drug loading was measured three times in parallel according to the method under "1.5.4", and the drug loading of MNs-TF-TA-PPa-PMs was found to be (0.96±0.028)%, and each piece of MNs-TF-TA-PPa-PMs contained (1.19±0.009) mg of drug.
[0216] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.
Claims
1. An active oxygen responsive tegafur-pyropheophorbide a conjugate soluble microneedle preparation, characterized in that: The TF-TA-PPa conjugate micelle solution, PSF, Arg8 and PVP-K90 are mixed by centrifugation, wherein the TF-TA-PPa conjugate micelle solution is prepared by dissolving the TF-TA-PPa conjugate and F68 in 55-64°C anhydrous ethanol, adding the solution dropwise to 55-64°C deionized water while stirring, and stirring at room temperature in the dark for 20-25 hours; The structural formula of the TF-TA-PPa conjugate is 2. The active oxygen responsive tegafur-pyropheophorbide a conjugate soluble microneedle preparation according to claim 1, characterized in that: The mass ratio of the TF-TA-PPa conjugate to the F68 is 1:
5.
3. The active oxygen responsive tegafur-pyropheophorbide a conjugate soluble microneedle preparation according to claim 1, characterized in that: The mass ratio of the PSF to PVP-K90 is 1-1.5:8.5-9.
4. The active oxygen responsive tegafur-pyropheophorbide a conjugate soluble microneedle preparation according to claim 3, characterized in that: The mass ratio of the PSF to PVP-K90 is 1:9 or 1.5:8.
5.
5. The active oxygen responsive tegafur-pyropheophorbide a conjugate soluble microneedle preparation according to claim 4, characterized in that: The added amount of Arg8 is 4-6% of the total mass of PSF and PVP-K90.
6. The active oxygen responsive tegafur-pyropheophorbide a conjugate soluble microneedle preparation according to claim 5, characterized in that: The added amount of Arg8 is 5% of the total mass of PSF and PVP-K90.
7. An active oxygen responsive tegafur-pyropheophorbide a conjugate soluble microneedle preparation according to any one of claims 1 to 6, characterized in that: The synthetic route of the TF-TA-PPa conjugate is:
8. Use of the active oxygen responsive tegafur-pyropheophorbide a conjugate soluble microneedle preparation according to any one of claims 1 to 7 in the preparation of an anti-tumor composition.
9. An antitumor composition, characterized in that: The active ingredient comprises the active oxygen responsive tegafur-pyropheophorbide a conjugate soluble microneedle preparation according to any one of claims 1 to 7.
10. An antitumor composition according to claim 9, characterized in that: The active ingredient is the active oxygen responsive tegafur-pyropheophorbide a conjugate soluble microneedle preparation.